A dictionary of weights, measures, and units / Donald Fenna - Donald Fenna (Oxford University Press, 2002)
This comprehensive and authoritative dictionary provides clear definitions of units, prefixes, and styles of weights and measures within the Système International (SI), as well as traditional, and industry-specific units. It also includes general historical and scientific background, covering the development of the sequential definitions and sizing of units. This new reference work will prove invaluable to professional scientists, engineers, technicians as well as to students and the general user